2018
DOI: 10.1002/jbm.b.34278
|View full text |Cite
|
Sign up to set email alerts
|

Effects of laser shock peening on the corrosion behavior and biocompatibility of a nickel–titanium alloy

Abstract: Nickel-titanium (NiTi) alloy is an attractive material for biomedical implant applications. In this study, the effects of laser shock peening (LSP) on the biocompatibility, corrosion resistance, ion release rate and hardness of NiTi were characterized. The cell culture study indicated that the LSP-treated NiTi samples had lower cytotoxicity and higher cell survival rate than the untreated samples. Specifically, the cell survival rate increased from 88 AE 1.3% to 93 AE 1.1% due to LSP treatment. LSP treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…This shows that there was a tendency to reduce the corrosion rate in all the laser peened samples in comparison to the unpeened Cu, whereas the highest performance in corrosion rate reduction was found at LSPVC 50 %. The results not only confirm that the LSP modification is optimum at LSPVC 50 % but also showed that the LSP process is an effective method for Cu corrosion mitigation [7,9,19,51].…”
Section: Iu Corr − Ip Corrsupporting
confidence: 56%
See 1 more Smart Citation
“…This shows that there was a tendency to reduce the corrosion rate in all the laser peened samples in comparison to the unpeened Cu, whereas the highest performance in corrosion rate reduction was found at LSPVC 50 %. The results not only confirm that the LSP modification is optimum at LSPVC 50 % but also showed that the LSP process is an effective method for Cu corrosion mitigation [7,9,19,51].…”
Section: Iu Corr − Ip Corrsupporting
confidence: 56%
“…In another development, the corrosion resistance of a biodegradable metallic implant (magnesium-calcium alloys) treated by LSP showed an increase in corrosion resistance by more than a 100-fold in simulated body fluid electrolyte as reported by Guo et al [18]. Similarly, Zhang et al [19] reported a wide positive shift in the corrosion potential of nickel-titanium alloy from − 440 mV to − 80 mV (a difference of − 360 mV) and reduction in corrosion current density from 1.41 to 0.67 μA cm − 2 for the untreated and the LSP treated surfaces respectively, tested in a simulated body fluid. This result by Zhang group was accompanied by an increase in hardness value from 226 to 261 HV due to the LSP treatment.…”
Section: Microstructural Characterizationmentioning
confidence: 67%
“…Sci. 2021, 11, 515 2 of 10 laser shock peening can increase the surface microhardness and enhance the mechanical property (such as wear-resistance) of NiTi alloy [13]. In our previous research, we also got similar results when the metals, such as aluminum, high strength, and NiTi alloy, were processed with laser shock peening [14][15][16].…”
Section: Introductionmentioning
confidence: 67%
“…Values of each material are given in Table 3. [66][67][68][69][70][71][72] For both anodic and cathodic behavior of a corroding material, electron transfer which is leading to electric current is directly associated in a corrosion process. Therefore, corrosion speed and rate depend on the releasing electron number and current flow between anodic and cathodic regions in a structure.…”
Section: Electrochemical Parameter Modeling For the Corrosion And Isr...mentioning
confidence: 99%